PERLINDUNGAN GOLPUT DALAM PERSPEKTIF HAM - Bakti, Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 1 (2015)DO - 10.24843/JMHU.2015.v04.i01.p06, 2015)
The existence of non-voters in the election to get the pros and cons in the community. Most people support but some of the group refused. In this study discussed the How arethe implications of abstentions in the democracy development in Indonesia? How is the human rights protection of the non-voters? This research is a normative legal materials sourced from primary and secondary legal materials. Legal materials collected qualitatively processed. Legal materials processing results are presented in descriptive analysis. Abstentions implications in the development of democracy in Indonesia is a hallmark of democracy itself that is the freedom to argue. Not voting is a choice that must be respected in a democracy in Indonesia. Protection of human rights of non-voters must be done by the state, the law and every person as the option to be non-voters are part of the political rights of the born first-generation rights. Rights in the first generation is not ruled out. Society needs to see that non-voters is an option that must be respected in democratic life. Option to not choose (non-voters) should be defined as a human right in the legislation in Indonesia.
Keywords: non-voters, human rights, democracy